The Later Fiction of Nadine Gordimer
X, 249 p.
Keywords: Nobel Prizewinner Nadine Gordimer's novels and short stories from The Conservationist to Jump have been her best and most controversial work. This new book examine such topics as the autobiographical basis of her fiction, her relationship to feminism, the place of the white woman in black Africa, the ambiguity of revolutionary politics, her ambivalent relationship to Judaism, her use of irony, the symbolism of landscape, and the ways in which she has revised recurring topics throughout her career as a writer.